2015
DOI: 10.1186/s12937-016-0151-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of breakfast consumption with body mass index and prevalence of overweight/obesity in a nationally-representative survey of Canadian adults

Abstract: BackgroundThis study examined the association of breakfast consumption, and the type of breakfast consumed, with body mass index (BMI; kg/m2) and prevalence rates and odds ratios (OR) of overweight/obesity among Canadian adults. These associations were examined by age group and sex.MethodsWe used data from non-pregnant, non-lactating participants aged ≥ 18 years (n = 12,377) in the Canadian Community Health Survey Cycle 2.2, a population-based, nationally-representative, cross-sectional study. Height and weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 32 publications
4
36
0
1
Order By: Relevance
“…On the other hand, the percentage of breakfast consumers in our study who reported smoking (43.3% and 32.6% in adults who ate breakfast “sometimes” and “always”, respectively) was lower than the proportion of smokers in the breakfast nonconsumers group (50.8%) (p<0.05). This is in agreement with other studies that had reported that breakfast skippers are more likely to have unhealthier habits, such smoking, than breakfast consumers [ 8 , 42 ]. In fact, it has been suggested that breakfast consumption may serve as a marker for a healthier lifestyle [ 34 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the percentage of breakfast consumers in our study who reported smoking (43.3% and 32.6% in adults who ate breakfast “sometimes” and “always”, respectively) was lower than the proportion of smokers in the breakfast nonconsumers group (50.8%) (p<0.05). This is in agreement with other studies that had reported that breakfast skippers are more likely to have unhealthier habits, such smoking, than breakfast consumers [ 8 , 42 ]. In fact, it has been suggested that breakfast consumption may serve as a marker for a healthier lifestyle [ 34 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, some prospective studies also showed that skipping breakfast is associated with a higher risk of body weight gain and incidence of obesity in US subjects . However, reports of Canadian adults show that skipping breakfast is not associated with prevalence of obesity . The differences may be due to the cultural differences among countries.…”
Section: Discussionmentioning
confidence: 98%
“…However, the association between skipping breakfast and obesity is controversial in adults. Some studies from the USA and Asia‐Pacific regions have shown that skipping breakfast is associated with obesity, whereas skipping breakfast has not been associated with the prevalence of obesity in Canadian adults . One of the reasons for these differences may be the cultural diversity across countries.…”
Section: Introductionmentioning
confidence: 99%
“…Breakfast is often touted as the most important meal of the day. While the evidence is less consistent for adult populations, the value of a healthy morning meal among youth is widely acknowledged. Regular breakfast consumption is associated with many positive outcomes for children and adolescents, including enhanced cognitive performance and learning‐related outcomes, improved diet quality (although this outcome likely depends on meal composition), increased physical activity levels, and positive psychosocial functioning .…”
mentioning
confidence: 99%